Coordination flexibility aided CO2-specific gating in an iron isonicotinate MOF - Singh, Himan Dev; Nandi, Shyamapada; Chakraborty, Debanjan; Singh, Kirandeep; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Chemistry-an Asian Journal, 2022)
Coordination flexibility assisted porosity has been introduced into an Iron-isonicotinate metal-organic framework (MOF), (Fe(4-PyC)(2) . (OH). The framework showed CO2-specific gate opening behavior, which gets tuned as a function of temperature and pressure. The MOF ` s physisorptive porosity towards CO2, CH4, and N-2 was investigated; it adsorbed only CO2 via a gate opening phenomenon. The isonicotinate, representing a borderline soft base, is bound to the hard Fe3+ centre through monodentate carboxylate and pyridyl nitrogen. This moderately weak binding enables isonicotinate to spin like a spindle under the CO2 pressure opening the gate for a sharp increase in CO2 uptake at 333 mmHg (At 298 K, the CO2 uptake increases from 0.70 to 1.57 mmol/g). We investigated the MOF ` s potential for CO2/N-2 and CO2/CH4 gas separation aided by this gating. IAST model reveals that the CO2/N-2 selectivity jumps from 325 to 3131 when the gate opens, while the CO2/CH4 selectivity increases three times. Interestingly, this Fe-isonicotinate MOF did not follow the trend set by our earlier reported Hard-Soft Gate Control (established for isostructural M2+-isonicotinate MOFs (M=Mg, Mn)). However, we account for this discrepancy using the different oxidation state of metals confirmed by X-ray photoelectron spectroscopy and magnetism.
Keywords: CO2 capture; flexible MOF; gating; Isonicotinic